PDIA2 Bridges Endoplasmic Reticulum Stress and Metabolic Reprogramming During Malignant Transformation of Chronic Colitis - Tao, Jie; Yin, Lin; Wu, Ao; Zhang, Jiaoli; Zhang, Jingpu; Shi, Huichun; Liu, Siyuan; Niu, Liangfei; Xu, Li; Feng, Yanling; Lian, Shixian; Li, Lei; et al. (Frontiers in Oncology, 2022)
Background: Chronic inflammation contributes to about 20% of cancers, the underlying mechanisms are still elusive. Here, using an animal model of colitis to colon cancerous transformation, we demonstrated that endoplasmic reticulum (ER) stress couples with metabolic reprogramming to promote malignant transformation of chronic inflammation. Methods: Animal model for chronic colitis to colon cancerous transformation was established in C57BL/6N mice by azoxymethane (AOM) and dextran sodium sulfate (DSS) treatments. The differential proteins in control and AOM/DSS-treated colon mucosa were determined using proteomic analysis; the kinetics of metabolic modifications were monitored by mitochondrial oxygen flux, extracellular acidification, and targeted metabolomics; the molecule linker between ER stress and metabolic modifications were identified by co-immunoprecipitation, KEGG pathway analysis, and subcutaneous tumor model using gene-specific knockdown colon cancer cells. Tissue array analysis were used to evaluate the differential protein in cancer and cancer adjacent tissues. Results: AOM/DSS treatment induced 38 tumors in 10 mice at the 14th week with the mean tumor size 9.35 ± 3.87 mm2, which was significantly decreased to 5.85±0.95 mm2 by ER stress inhibitor 4-phenylbutyric acid (4PBA). Seven differential proteins were determined from control (1067 ± 48) and AOM/DSS-treated mucosa (1077 ± 59), the level of ER protein (protein disulfide-isomerase A2 (PDIA2)) was increased over 7-fold in response to AOM/DSS treatment. PDIA2 interacted with 420 proteins that involve in 8 signaling pathways, in particular with 53 proteins in metabolic pathways. PDIA2 translocated from ER to mitochondria and interacted with components of complexes I and II to inhibit oxophosphorylation but increase glycolysis. Knockdown PDIA2 in colon cancer cells restored the metabolic imbalance and significantly repressed tumor growth in xenograft animal model. 4PBA therapy inhibited AOM/DSS-mediated over-expression of PDIA2 and metabolic modifications, and suppressed colon cancer growth. In clinic, PDIA2 was over-expressed in colon cancer tissues rather than cancer adjacent tissues, and was related with late stages and lymph node metastasis of colon cancer. Conclusions: Persistent ER stress reprograms metabolism to promote malignant transformation of chronic colitis, PDIA2 serves as a molecule linker between ER stress and metabolic reprogramming. Inhibition of ER stress restores metabolic homeostasis and attenuates cancerous transformation of chronic inflammation.